Southern Chinch Bug, Blissus insularis Barber (Insecta: Hemiptera: Lygaeidae) - Stacy Woods (EDIS)
This EDIS publication is an alternate version of a page published first on the Featured Creatures website. The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. This 5-page fact sheet sheet that discusses the southern chinch bug was written by Stacy Woods and published by the UF Department of Entomology and Nematology, August 2001.